Land Acquisition, Peasant Exclusion, and People Resistance Advocacy at Bolok Industrial Area in Kupang, East Nusa Tenggara, Indonesia - Dhosa, Didimus Dedi (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2019)
This study aims to investigate industrial development project by corporations facilitated by the government of East Nusa Tenggara Province. The government argues that the development of Bolok Industrial area can open workforce, elevate the welfare of citizens, and reduce the poverty index. This research was conducted from February to July 2019. Data collection techniques are indepth interview, focus group discussion, and participant observation. By using a critical qualitative approach and a Marxian analysis of land acquisition and capital accumulation, this paper finds four urgent things. Firstly, people’s land is grabbed by corporations with government’s support. Secondly, the acquisition is carried out with the politics of 'lure' and 'tourism' to the island of Java. Thirdly, land acquisition causes inequality in land tenure and exclusion of farmers from their arable land. Fourthly, advocacy of critical awareness by various actors becomes less effective when important actors in society have been co-opted by corporations which resulted in conquering to the masses. The government of NTT Province must reconsider the development of an industrial area if they don’t want local people to be trapped in the poverty circle and ecological destruction.